Pretreatment BMI Is Associated with Aggressive Clinicopathological Features of Papillary Thyroid Carcinoma: A Multicenter Study - Shi-tong Yu; Wanzhi Chen; Qian Cai; Faya Liang; Debin Xu; Ping Han; Jichun Yu; Xiaoming Huang (International Journal of Endocrinology)
Objectives. The aim of the present study was to analyze the association between pretreatment body mass index (BMI) and the aggressiveness of papillary thyroid carcinoma (PTC) along with its clinical outcomes in a Chinese population with BMI classification for Asians. Methods. A retrospective, observational study was conducted on patients from two teaching hospitals in China. 1622 classical PTC patients were categorized into four groups according to BMI. Results. We found that increased BMI was associated with extrathyroidal extension, multifocality, the presence of lymph node (LN) metastasis, and advancing TNM stage in PTC patients. Furthermore, compared to patients with normal weight, those in the overweight and obese group exhibited a significantly increased risk of extrathyroidal extension, multifocality, cervical LN metastasis, and advanced TNM stage. 40 and 37 patients experienced persistent and recurrent disease, respectively. No differences regarding persistent disease or recurrence were observed among the BMI groups. Conclusion. A higher pretreatment BMI has been strongly associated with aggressive features of PTC according to the BMI classification for Asians. Obesity was not found to be associated with a greater risk of recurrence.